Analysis of endoplasmic reticulum of tobacco cells using confocal microscopy - Radochová, Barbara (Image analysis and stereology, 2005)
Image analysis techniques for preprocessing, segmentation and estimation of geometrical characteristics of fiber-like structures from 2-D or 3-D images captured by a confocal microscope are presented. Methods are demonstrated on fiber-like biological structure: endoplasmic reticulum (ER) of tobacco cells. In the presented analysis of 2-D images of ER before and after the treatment of latrunculin B, ER and ER tubules were segmented and the area density of ER as well as the length density of ER tubules in the cell cortical layer were estimated by automatic image analysis algorithms. Images of 3-D arrangement ofER were reconstructed and rendered by various visualization techniques.
Keywords: Endoplazemski retikulum; Tobacco; Ultrastructure; Mikroskopija konfokalna; Slika, obdelava z računalnikom; Endoplasmic Reticulum; Microscopy, Confocal; Tobak; Image Processing, Computer-Assisted; citologija; stereologija; mikroskopija; endoplazmatski retikulum